Gendering modern German history : rewriting historiography - Hagemann, Karen; Quataert, Jean H. (Jean Helen), 1945- (Berghahn Books, 2007)
Writing on the history of German women has - like women's history elsewhere - undergone remarkable expansion and change since it began in the late 1960s. Today Women's history still continues to flourish alongside gender history but the focus of research has increasingly shifted from women to gender. This shift has made it possible to make men and masculinity objects of historical research too. After more than thirty years of research, it is time for a critical stocktaking of the ""gendering"" of the historiography on nineteenth and twentieth century Germany. To provide a critical overview.